Effects of estuary reopening management on the fish community in the Nakdong River Estuary - Hong, Donghyun; Gim, Jeong-Soo; Joo, Gea-Jae; Kim, Dong-Kyun; Choi, Daehyun; Lee, Hak-Young; Jeong, Kwang-Seuk; Jo, Hyunbin (Frontiers in Marine Science, 2024)
Estuary reopening is a means of restoring estuarine habitats, which has recently been implemented in a few developed countries. The regeneration of a brackish zone in the Nakdong River Estuary (NRE), South Korea, were tested through a series of barrage reopening. During the same period, we conducted extensive fish surveys in the upper part of the NRE barrage on a monthly basis from 2017 to 2021, and subsequently determined whether fish populations and communities were affected by the reopening. The results showed that the reopening of the NRE hardly affected the fish community structure, as non-native species such as Erythroculter erythropterus and Lepomis macrochirus maintained their dominance. Still, we discovered that certain euryhaline species are positively affected by estuary reopening, as total 46 Japanese eels (Anguilla japonica) were captured after the reopening, which had not been detected before the reopening. By comparing the size structure of various fish species, we discovered that size distribution of native and migratory species presented more positively skewed pattern after the reopening, while size structure in non-native species remained relatively unchanged normally distributed pattern. Piecewise structural equation modelling revealed that the NRE had become more complex ecosystem, as migratory fish species abundance and biomass started to show a positive correlation with hydraulic factors such as discharge and negative correlation with seasonality after the reopening. We concluded that estuary reopening created some changes in migratory and native freshwater species but such changes were not notably detected in non-native species. Therefore, appropriate sluice operation methodologies, such as considering the migration seasons of migratory species, should be developed. Additionally, human-involved management policies are required to regulate non-native species populations.